Lemish, D., Gotz, M. (2017). "Beyond the Stereotypes? Images of boys and girls, and their consequences". The International Clearinghouse on Children, Youth and Media, Yearbook 2017. Gothenburg: NORDICOM, Sweden, 254 páginas. ISBN: 0-7507-0596-5 (pdf). - Ponte, Cristina (Sociedad e Infancias, 2018)